Profesionalisme Marine Inspector dalam Mewujudkan Keselamatan Pelayaran Menuju Zero Accident di Pelabuhan Kelas Utama Tanjung Perak - Kusumawati, Elly; Asdiana, Femmy; Lestari, Elise Dwi (Departemen Teknik Kelautan Universitas Hasanuddin, 2024)
This study examines the important role of Marine Inspectors in ensuring voyage safety and towards Tanjung Perak Surabaya Main Class Port Zero Accident. It examines the professionalism of Marine Inspectors in checking the seaworthiness of ships to sail. This study also analyzes the challenges faced by Marine Inspectors in conducting inspections. The method uses by the researchers is qualitative research methods. The study used observation and interview methods to obtain data. This study found that the ship inspection procedure carried out by the Marine Inspector is in accordance with the procedure. The inspection is not only carried out on the ship's body, but also related machinery and certificates that must be owned before sailing. The processing of these certificates can also be done online through SIMKAPEL. SIMKAPEL is a web-based database to assist certificate processing without having to come to Tanjung Perak Surabaya Main class Port. The professionalism of the Marine Inspector is required to keep the inspection in accordance with the procedure. Professionalism is needed so that every ship sailing can be guaranteed to be seaworthy to minimize the occurrence of accidents while sailing. Although it has been done properly and according to procedure, there are still challenges experienced by Marine Inspectors in conducting inspections. The challenges faced by Marine Inspectors in conducting inspections are adverse weather, lack of attachments from shipowners for ship inspections, and lack of personnel to conduct ship inspections.